Greening the G7 economies through a more inclusive Climate Club - Edward Barbier (Asian Development Bank Institute (ADBI), 2023)
Despite some progress, the Group of Seven (G7) have yet to act collectively to foster a low-carbon transition of their economies. This paper outlines such a strategy, which would also encourage other economies to follow suit. This strategy has three elements. First, the G7 should agree to end the underpricing of fossil fuels, including phasing out subsidies and phasing in taxes or tradable permits to cover the costs of local air pollution, global warming, and other damages. Second, any revenues saved or raised should be recycled to fund green innovation or additional measures to offset any adverse income or employment effects of a clean energy transition. Third, the G7 should require that fossil fuel pricing reforms are the main precondition for joining its proposed Climate Club and should impose a levy on carbon- intensive imports to encourage compliance by other countries. The G7 should also provide comprehensive assistance to emerging market and developing economies to help accelerate their clean energy transition, facilitate their eventual participation in the Climate Club, and foster the attainment of climate, poverty, and development goals that also promote strong and resilient economies.
Keywords: Q54; Q58; F18; O44; 330; clean energy; carbon levy; climate club; fossil fuel pricing; green innovation; Joint Energy Transition Partnership; low-carbon transition; Partnership for Global Infrastructure and Investment